Qualitative and quantitative study of police investigative thinking styles. (27th February 2007) - Dean, Geoff; Fahsing, Ivar Andre; Gottschalk, Petter
A qualitative study of detectives' investigative thinking in Australia identified four thinking styles: method style, challenge style, skill style and risk style. Multiple item scales were developed for these four constructs in a survey instrument. A quantitative study based on the questionnaire was conducted among detectives in Norway. None of the multiple item scales achieved acceptable reliability. Factor analysis suggests a number of new thinking styles, including entrepreneur style and architect style.